The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/rjta-05-2020-0044
|View full text |Cite
|
Sign up to set email alerts
|

The parameters affecting seam quality: a comprehensive review

Abstract: Purpose The conversion of fabric into a garment involves many interactions such as the selection of suitable sewing thread, optimization of sewing parameters, ease of conversion of fabric into the garment and actual performance of the sewn fabric during wear of the garment. The adjustment of all sewing parameters is necessary to ensure quality. The purpose of this paper is to define the parameters that affect seam quality comprehensively. Design/methodology/approach This study primarily focuses on the studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…To assess the effect of sewing thread on seam quality, 100% polyester corespun and 100% mercerised cotton sewing threads were selected. The main reason for choosing them was that the sewing threads used in the garment industry are generally produced from cotton and polyester fibres [30]. Especially polyester corespun sewing threads dominate the market due to their very high yarn strength property [21] and are suitable for the production of normal clothing products thanks to their versatile structure [10].…”
Section: Sewing Threadmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effect of sewing thread on seam quality, 100% polyester corespun and 100% mercerised cotton sewing threads were selected. The main reason for choosing them was that the sewing threads used in the garment industry are generally produced from cotton and polyester fibres [30]. Especially polyester corespun sewing threads dominate the market due to their very high yarn strength property [21] and are suitable for the production of normal clothing products thanks to their versatile structure [10].…”
Section: Sewing Threadmentioning
confidence: 99%
“…The sewing needle, one of the seam forming elements, is essential to ensure good seam quality. Especially choosing the right needle size and needle point is one of the most important parameters in the production of garments' joints [11,14,30,38]. As the existing literature proves the significant effect of needle size on seam quality, the thicker needles decrease the seam strength, seam efficiency and seam elongation, whereas increase the force required to pierce the needle through the fabric [12,15].…”
Section: Sewing Parametersmentioning
confidence: 99%
“…Even if the fabric is still intact, a seam failure might render the garment unfit for regular wear [20]. https://doi.org/10.31881/TLR.2021.34 Indeed, many studies have been carried out to determine seam strength based on various parameters [21][22][23][24][25][26][27]. However, some studies showed a linear relationship between seam strength and stitch density, as all used a very low stitch density of 7 to 13 stitches per inch [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Sewing damage has been studied extensively since the 1950s. [1][2][3][4][5][6] Attention to this problem has also been paid in manufacturing industrial textiles and composites. [7][8][9] Dorkin and Chamberlain have pointed out that unsatisfactory seams are most likely due to either yam slippage or yarn breakage.…”
mentioning
confidence: 99%
“…Most of the studies have focused on the influence of sewing parameters, such as needle resistance force, needle thickness, sewing thread linear density, fabric structures, and fabric type on the seam strength and damage to the yarns in the fabric. 1,[3][4][5][6][10][11][12][13] Unfortunately, little has been reported about controlling sewing damage in the form of yarn splitting due to insertion of the sewing needle tip that pushes aside the neighboring yarns, forming cracks perpendicular to the sewing line in the fabric, as shown in Figure 1. On the other hand, fabrics woven with continuous filament yarns such as cuprammonium fabrics become more and more popular because they have unique properties such as good handling, air permeability, antistatic, and other good characteristics.…”
mentioning
confidence: 99%